Emergency remote teaching in stricto sensu graduate courses during the covid-19 pandemic: a reflection study - Santos, Andressa Silva Torres dos (2024)
Objective: to reflect on remote teaching, used during the covid-19 pandemic, in stricto sensu graduate studies in the university context. Method: this is a reflection study, supported by a bibliographical survey that allowed the recognition of the predominance of the technical focus, analyzed in the light of authors whose theoretical framework articulates education and university with social relations. Results: the analysis of remote teaching demands an investigation into its relationship with changes that have been taking place at universities in the neoliberal scenario, valuing education and society projects with a marketing focus, influencing knowledge production, researcher and professor training. Conclusion: going beyond the technical dimension to appropriating the ethical-political dimension present in remote teaching and its possible post-pandemic developments is fundamental, as the educational act’s potential, in terms of the meeting between professor and student and appropriation of knowledge, is not effectively achieved in remote teaching.